How Brian Brock’s Hermeneutic of Disability is Relevant to All Marginalised Bodies - Bowen-Evans, Kate (Journal of disability & religion, 2022)
Normate hermeneutics is the interpretation of the Bible based on unconscious and implicit beliefs on what is “normal”. The label “disabled” is itself often contrasted with the idea of normalcy in biblical interpretation. A hermeneutic of disability allows the experience of those labeled disabled to frame biblical analysis. Building on Brian Brock’s hermeneutic of disability I show how the body imagery of 1 Corinthians 12 helps to understand the redeemed social dynamics of the church and how each member is understood to be part of Christ’s resurrected body in the world unrelated to their bodily form in life. God gives greater honor to those body parts or body types the world degrades. The relevance of this understanding reaches beyond the categories of abled or disabled. The vulnerable body of the crucified Christ is God’s chosen form to reveal God’s wisdom. In both his body and his actions Jesus subverted social norms that exclude. My concern is those whose bodies may not be considered disabled, but whose experiences of their bodies might be best understood in light of disability hermeneutics. I suggest that God creates all bodies fit for relationship, and God does not see some as more weak or unpresentable than others, which suggests that the disability hermeneutic is relevant to all marginalized bodies. I argue that this disability hermeneutic has a liberating effect for more than just those labeled disabled, but provides affirmation for anyone whose body is considered weak or inferior, disabled or deviant in their society.